Does carbon emission trading policy induce financialization of non-financial firms? Evidence from China - Zhang, Xiaoliang; Zheng, Xiaojia (Energy economics, 2024)
The carbon emission trading scheme influences firms’ operation costs, which may induce resource diversion to financial investments. By using a sample of Chinese A-share non-financial listed firms that are subject to carbon emission trading pilot programs in China, this paper employs a differences-in-differences analysis to test the impact of carbon emission trading on firms’ financial asset allocation. We find that carbon emission trading significantly increases corporate financialization, especially long-term financial assets. The effect is stronger in firms with stronger profit-seeking incentives and weaker governance, suggesting the mechanism of capital profit-seeking and management opportunism under increased operation costs and risk. Further heterogeneity analysis indicates that the positive association between carbon emission trading and corporate financialization is more pronounced in non-state-owned enterprises, carbon-intensive firms, and firms in regions with developed financial markets or more volatile carbon markets. •Carbon emission trading significantly increases corporate financialization.•This effect is larger in firms with more profit-seeking motives and weaker governance, supporting investment substitution.•The effect is stronger in carbon-intensive firms and firms facing developed financial markets or volatile carbon markets.